Toll-like receptor agonists shape the immune responses to a mannose receptor-targeted cancer vaccine - He, Li-Zhen (Cell Mol Immunol, 2015)
Previous studies have documented that selective delivery of protein antigens to cells expressing mannose receptor (MR) can lead to enhanced immune responses. We postulated that agents that influenced the MR expression level, and the activation and migration status of MR-expressing antigen presenting cells, would modulate immune responses to MR-targeted vaccines. To address this question, we investigated the effect of clinically used adjuvants in human MR transgenic (hMR-Tg) mice immunized with an MR-targeting cancer vaccine composed of the human anti-MR monoclonal antibody B11 fused with the oncofetal protein, human chorionic gonadotropin beta chain (hCGβ), and referred to as B11-hCGβ. We found that humoral responses to low doses of B11-hCGβ could be enhanced by prior administration of GM-CSF, which upregulated MR expression in vivo. However, co-administration of the Toll-like receptor (TLR) agonists, poly-ICLC and/or CpG with B11-hCGβ was required to elicit Th1 immunity, as measured by antigen-specific T-cell production of IFN-γ. The TLR agonists were shown to increase the number of vaccine-containing cells in the draining lymph nodes of immunized hMR-Tg mice. In particular, with B11-hCGβ and poly-ICLC, a dramatic increase in vaccine-positive cells was observed in the T-cell areas of the lymph nodes, compared to the vaccine alone or combined with GM-CSF. Importantly, the absence of the TLR agonists during the priming immunization led to antigen-specific tolerance. Therefore, this study provides insight into the mechanisms by which adjuvants can augment immune responses to B11-hCGβ and have implications for the rationale design of clinical studies combining MR-targeted vaccination with TLR agonists.